PROGNOSTIC SIGNIFICANCE OF VISIT-TO-VISIT VARIABILITY, MEAN AND MAXIMUM BLOOD PRESSURE IN TREATED HYPERTENSIVE PATIENTS WITH HIGH CARDIOVASCULAR RISK. (June 2018) - Tasic, I.; Kostic, S.; Djordjevic, D.; Bogdanovic, D.; Bastac, D.; Lovic, M.; Stoickov, V.; Lovic, D.
Abstract : Objective: Associating the visit-to-visit variability (VVV) of systolic BP (SBP), mean and maximum SBP with cardiovascular disease (CVD) and mortality outcomes in treated hypertensive patients with high CV risk. Design and method: This prospective study included 142 hypertensive patients (65% females), with high CV risk defined with ESH score, mean age 63.1 ± 8 years, in the beginning, the office blood pressure was 155.5 mmHg. Each participant was followed over a period of time of 6.2 years and BP measurements 6 or more visits; follow-up for CVD or mortality outcomes. The VVV of SBP was defined as the standard deviation (SD), coefficient variation (CV) and across SBP measurements obtained at 6 or more visits conducted. Results: SD SBP was 14.5 ± 4, CV SBP 10.1 ± 3, mean SBP 145.8 ± 14 and max SBP 166.1 ± 17 mmHg. During the follow-up period, the incidence of non-fatal and fatal CV events was 19.7%, CV mortality 7%, and total mortality 9.9%.The effects of SD, CV, mean and maximum SBP on study outcomes were estimated by using a Cox proportional hazards model, unadjusted (model 1), with adjustment for age, sex, number of anthypertensive-drugs, and DM (model 2), or with additional adjustment for current smoking, heart rate, total cholesterol, triglycerides and body mass index (model 3). Mean, SD, CV, and maximum SBP were analyzed as continuous variables with hazard ratios (HRs) and 95% confidence intervals (CIs) shown per increase of 1 mgHg for each parameter. Total and CV mortality risk were significantly and positively associated with mean SBP during the measurement period (HR:1.043, 95%CI 1.01-1.077, P = 0.011);(HR:1.047, 95%CI 1.09-1.086, P = 0.014), while associations between total and CV mortality risk and SD, CV and maximum SBP were not statistically significant. Major CV events risk were positively associated with mean (HR:1.038, 95%CI 1.016-1.061, p < 0.001); SD (HR: 1.108, 95%CI 1.025-1.198, P = 0.010; CV (HR: 1.172, 95%CI 1.029-1.334, P = 0.017); and maximum SBP (HR: 1.032, 95%CI 1.010-1.054, P = 0.004); (model 1). These associations remained essentially unchanged after adjustments for other factors (models 2 and 3). Conclusions: In our study VVV has been associated with cardiovascular disease but not with mortality.